The Research Lab as Satellite Library - Mason Brown (Issues in Science and Technology Librarianship, 2020)
It is challenging to identify the needs of researchers and students at any satellite campus, a situation that is exacerbated when the satellite library is a research laboratory. The users are not taking classes, but still have library support needs. This article discusses the difficulties in properly identifying a population of students at this type of institution, as well as the associated challenges that come with developing a series of library workshops for different groups of users.